(untitled) (Revista Contexto & Saúde, 2026)
Objective: To evaluate the association between Post-COVID-19 Syndrome and quality of life among quilombola populations in the municipality of Santarém, Pará, Brazil. Method: This cross-sectional quantitative study was conducted in the quilombola communities of Tiningu and Murumuru between August and September 2023. Initially, 32 individuals with documented or suspected post-COVID conditions were identified. After applying eligibility criteria, persistent symptoms for at least 12 weeks and exclusion of individuals with pre-existing conditions that could interfere with the assessment, the final sample comprised 25 participants. Data were collected through face-to-face interviews conducted in Portuguese, using standardized reading of response options. Health-related quality of life was assessed using the EQ-5D-5L instrument, which evaluates five dimensions (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression), along with the Visual Analogue Scale (VAS; range: 0-100) for self-perceived health status. Data analysis included descriptive statistics and association tests (p < 0.05), with comparisons of VAS scores across EQ-5D-5L dimension levels performed using the Kruskal–Wallis test. Logistic regression models (for categorized VAS scores) and linear regression models (for continuous VAS scores) were also applied. Results: Significant impairment was observed across multiple dimensions of quality of life, particularly regarding moderate pain/discomfort, reported by 56.0% of participants, as well as substantial limitations in mobility and usual activities. The mean VAS score was 63.3 (SD = 22.3), with a median of 70, indicating an intermediate overall perception of health. A negative correlation was identified between the severity of impairment across EQ-5D-5L dimensions and VAS scores (r = -0.44), suggesting a poorer perception of health as the burden of functional limitations increased. Conclusion: Among quilombola individuals affected by Post-COVID-19 Syndrome, evidence of reduced quality of life was observed, particularly in relation to pain/discomfort and functional aspects. These findings underscore the need for continued follow-up and targeted rehabilitation and mental health interventions within primary healthcare services, taking into account the specific vulnerabilities of these territories.